2009
DOI: 10.1063/1.3089687
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the high diode-ideality factors in GaInN/GaN multiple quantum well light-emitting diodes

Abstract: We report on a significant decrease in the diode-ideality factor of GaInN/GaN multiple quantum well light-emitting diodes (LEDs), from 5.5 to 2.4, as Si-doping is applied to an increasing number of quantum barriers (QBs). The minimum ideality factor of 2.4 is obtained when all QBs are doped. It is shown that polarization-induced triangular band profiles of the undoped QBs are the major cause of the high ideality factors in GaInN/GaN LEDs. Numerical simulations show excellent agreement with the measured idealit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(97 citation statements)
references
References 16 publications
2
93
0
2
Order By: Relevance
“…[ 41 ] The relation between the ideality factor and recombination processes in p-n junctions have been well-studied, both recently in organic photovoltaics [42][43][44] and for over 50 years in inorganic p-n junctions. [45][46][47][48] The diode ideality factor was fi rst introduced by W. Shockley and colleagues in order to quantitatively describe the effect of Shockley-Read-Hall recombination in the bulk (as opposed to the interfaces) of a p-n junction. [ 46 ] The effect of recombination on the diode current through surface or interface states has also been observed to lead to deviations of the 'ideal' ideality factor ( n = 1) to the non-ideal case ( n = 2).…”
Section: Increase In Recombination Due To Addition Of Pc 84 Bm Trap Smentioning
confidence: 99%
“…[ 41 ] The relation between the ideality factor and recombination processes in p-n junctions have been well-studied, both recently in organic photovoltaics [42][43][44] and for over 50 years in inorganic p-n junctions. [45][46][47][48] The diode ideality factor was fi rst introduced by W. Shockley and colleagues in order to quantitatively describe the effect of Shockley-Read-Hall recombination in the bulk (as opposed to the interfaces) of a p-n junction. [ 46 ] The effect of recombination on the diode current through surface or interface states has also been observed to lead to deviations of the 'ideal' ideality factor ( n = 1) to the non-ideal case ( n = 2).…”
Section: Increase In Recombination Due To Addition Of Pc 84 Bm Trap Smentioning
confidence: 99%
“…The lowest (highest) IF suggests the decreased (increased) defect densities in MQW, which always serve as nonradiative recombination centers [16]. The optimized ideality factor of 1.41 is dramatically lower than previous reports [15,17]. Moreover, C-V measurements are performed.…”
Section: Resultsmentioning
confidence: 92%
“…16 Values of n as high as 7.0 have been found, however, for InGaN/GaN diodes; high ideality factors appear for nitride-based p-n junction diodes when the temperature is below 300 K. 12 Shah et al 12 proposed that GaN-based LEDs can be modeled as a series of rectifying unipolar heterojunctions and metal-semiconductor junctions, each having an associated ideality factor. From modeling of the I-V characteristics, 17 Zhu et al found recently that the externally measured ideality factor of a p-n junction diode is the sum of the ideality factors of the individual rectifying junctions within the diode. This dependence reveals that the ideality factors of the individual rectifying junctions add up to the total device ideality factor when considering the p-n junction of the diode, a nonohmic metal-semiconductor junction, or any other rectifying junction.…”
Section: Resultsmentioning
confidence: 99%